BOARD CHARACTERISTICS AND ENVIRONMENTAL INFORMATION DISCLOSURE OF LISTED MANUFACTURING FIRMS IN NIGERIA - Okere, Wisdom; Rufai, Oluwatobi; Okeke, Obiajulu Chibuzo; Oyinloye, Josephine Bola (Journal of Business And Entrepreneurship, 2021)
The paper analysed the relationship amid board characteristics and environmental information disclosure of listed Nigerian manufacturing firms. The data used were sourced from twenty (20) Nigerian listed companies from the manufacturing sectors, which were randomly chosen from manufacturing firms listed on the Nigerian stock market between 2013 and 2017. The study made use of ordinary least squares regression. According to the research findings, there exists a positive and significant relationship linking board independence and environmental disclosure in Nigeria’s oil and gas and manufacturing sectors. In line with the results, a large board of directors comprised of foreign directors would improve firms’ environmental disclosure. Furthermore, this study’s findings would help organisations satisfy stakeholders’ needs in their corporate governance practices. This study throws light on voluntary disclosures and how firms can adjust their corporate governance practices to boost their environmental disclosures, which is a contemporary issue because stakeholders demand more information that affects their investing decisions.